PBAT biodegradable mulch films: Study of ecotoxicological impacts using Allium cepa, Lactuca sativa and HepG2/C3A cell culture - Souza, Patrícia Moraes Sinohara; Sommaggio, Lais Roberta Deroldo [UNESP]; Marin-Morales, Maria Aparecida [UNESP]; Morales, Ana Rita (Elsevier, 2020)
Biodegradable mulch films are an alternative to polyethylene films used in agriculture for weed control, improving crop productivity. This change could minimize the residue production and costs related to the final disposal. Nevertheless, the environmental safety of these biodegradable products is scarcely investigated. In this work, samples of poly(butylene adipate-co-terephthalate)-PBAT mulch films, with and without UV stabilizer additives, were prepared. Aqueous extracts of soil samples, where mulch films were disposed, were investigated using bioassays with Lactuca sativa, Allium cepa, and cell culture HepG2/C3A. As PBAT is expected to suffer photodegradation and biodegradation, soil samples mixed with films before and after these processes were evaluated. Soil aqueous extracts promoted root grown (mainly hypocotyl) of L. sativa, probably due to presence of nutrients. So, to evaluate toxicity potential, in this case it was necessary to use aqueous extract prepared with soil instead of ultrapure water as the control. After doing this analysis it was observed that no adverse impacts due to PBAT films occurred. No chromosomal abnormalities were observed in A. cepa bioassay for any of tested samples. The absence of genotoxic potential was confirmed by comet assay and micronucleus test using human hepatocarcinoma cell line HepG2/C3A. These results showed that the soil did not induce damage to the tested organisms, before and after degradation of PBAT films.
Keywords: Biodegradable mulch films; Cytotoxicity; Genotoxicity; Human cell line; Plant bioindicators; poly(butylene adipate co-terephthalate)